A ciência que veio da lama: uma abordagem etnoecológica das relações ser humano/manguezal na comunidade pesqueira de Acupe, Santo Amaro-BA - Souto, Francisco José Bezerra (2004)
Mangrove ecosystems have a high biomass and biodiversity concentration. High productivity supports the exploitation by many traditional populations that survive on shellfish s catching and artisanal fishery, like those who live in the Acupe District, located in Santo Amaro, in the west coast of the Todos os Santos Bay (Bahia State, Northeast Brazil). Many resources are exploited locally, such as swimming crabs, crabs, bivalves and a great variety of fishes. The objective of this work was to study the shellfish catching and fishery under the Marques broad ethnoecological approach. It was used as a focal reference, aiming to identify the basic connections between human beings and mangrove ecosystem. Semi-structured interviews were conducted with shellfishwomen and fishermen, in order to know thinkings (knowledge and beliefs) and behaviors involved in many exploitation modalities. Direct observation of the informants daily working activities was also accomplished. Photographic recording was made during these activities, aiming to produce a visual ethnography. The results were analysed with a combined etic-emic approach, by comparing folk and scientific knowledge. The observed traditional behavior was correlated to possible environmental implications. It was observed a significant body of traditional knowledge about classification, trophic ecology, morphology, physiology, phenology, ecozonation and hydrodynamics, as well as about mangrove ecosystem dynamics. In some cases, this knowledge was compatible to those accepted by academic ones. The five basic connections predicted by the Marques approach were evidenced in the local shellfishing and fishery. Fishers interactions with minerals, plants, animals, human beings and supernatural elements revealed perception and utilization ways strongly associated to local culture, with important environmental implications.